The protectiing law of the foreign investments in countries of development : example West africa - (:unkn) unknown (My University, 2018)
"The protection of foreign direct investment in developing countries: the example of West Africa"FDI is at the heart of globalization and north-south economic relations. The question of their protection and legal regulation is acute. Faced with the scarcity of other sources of development finance (development aid) and the difficulties of access to technology, FDI is an important resource for filling the insufficiency of internal resources. This is why African countries in general, and those in West Africa in particular, are competing vigorously to receive foreign capital by providing them with an attractive, secure and non-discriminatory legal and institutional framework. Indeed, in the West African subregion, the law is used by States, but also by subregional integration organizations such as ECOWAS as an important instrument for demonstrating economic attractiveness. Thus, the analysis and measurement of the legal and institutional framework for FDI in West Africa will be discussed. In other words, has the security dimension of the investment (reception, processing, guarantee and settlement of disputes etc.) allowed for greater promotion and reception of investments from these countries?The interest of the subject is multiple. Indeed, at the legal and academic level, it allows to know, analyze and situate the entire legal regime of foreign investment at the internal level (investment code, mining code, oil code). At the external level, there is a multitude of conventions - such as bilateral BIT investment treaties -, accession to the relevant international investment conventions, and of course the increasingly visible and visible role of Community law in through the "communitisation of the law of foreign direct investment". The study of this subject shows the deep gap that exists between theory and practice in the FDI legislation of the countries of this part of Africa. If, upstream, the texts are more or less similar to those of the advanced countri
Keywords: African Research